Quality management of laser cladding processes for additive manufacturing by new methods of visualisation and evaluation of thermographic data. Issue 1 (2nd January 2020) - Wargulski, Dan Ralf; Nowak, Torsten; Thiele, Magnus; Dobbelstein, Henrik; Dillkötter, David; Stoppok, Johann; Schacht, Ralph; Abo Ras, Mohamad
ABSTRACT: Additive manufacturing by laser cladding is a promising tool for rapid prototyping, construction of bionic structures and replacement part production. To ensure a constant quality of manufactured components and to shorten the development process between CAD model and suitable produced components quality management and process monitoring system is inevitable. Therefore, a system has been developed to evaluate the cladding process by means of thermographic measurements. Melt pool temperature measurements by a thermal imaging camera have been processed to 2- and 3-dimensional temperature maps of the manufactured component. Analogous to tomographic images, these maps easily reveal weak spots in the process and flaws in the component itself. The quality management system was tested and evaluated on several laser-cladding processes with various defects on specially designed test structures.